2000
DOI: 10.1002/1097-0142(20000715)89:2<276::aid-cncr11>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Microwave coagulation therapy for multiple hepatic metastases from colorectal carcinoma

Abstract: BACKGROUND Compared with other treatments, microwave coagulation is a relatively less invasive treatment for various kinds of solid tumors. Although its effectiveness in primary hepatocellular carcinoma has been shown, its effectiveness in the treatment of hepatic metastases from colorectal carcinoma has been unclear. The aim of this study was to evaluate its effectiveness in the treatment of multiple hepatic metastases from colorectal carcinoma by comparing this technique with that of hepatic resection. METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
138
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(147 citation statements)
references
References 34 publications
2
138
0
5
Order By: Relevance
“…Patients with up to 5 liver metastases and a size of ≤ 4 cm are eligible candidates for local ablation. As previously mentioned, comparable survival results to surgical resection can be reached using different ablation techniques for colorectal cancer liver metastases [23]. In a retrospective analysis Eng et al treated 49 tumors (0.5 to 5.5 cm in size) in 33 patients who underwent intraoperative MWA of colorectal cancer liver metastases [49].…”
Section: Mwa Results In Liver Metastasesmentioning
confidence: 94%
See 1 more Smart Citation
“…Patients with up to 5 liver metastases and a size of ≤ 4 cm are eligible candidates for local ablation. As previously mentioned, comparable survival results to surgical resection can be reached using different ablation techniques for colorectal cancer liver metastases [23]. In a retrospective analysis Eng et al treated 49 tumors (0.5 to 5.5 cm in size) in 33 patients who underwent intraoperative MWA of colorectal cancer liver metastases [49].…”
Section: Mwa Results In Liver Metastasesmentioning
confidence: 94%
“…A study by Shibata et al compared the survival between surgical resection and MWA of colorectal cancer liver metastases. The 1-, 2-, and 3-year survival rates and mean survival times were 71 %, 57 %, 14 %, and 27 months, respectively, in the microwave group, whereas they were 69 %, 56 %, 23 %, and 25 months, respectively, in the hepatectomy group [23]. Complete tumor ablation near major vessels can be difficult to achieve.…”
Section: Indication For Mwamentioning
confidence: 87%
“…Of all the studies included in our systematic review, there was only one RCT in the MWA group 13 and one case-control prospective study in the CA group.…”
Section: Resultsmentioning
confidence: 99%
“…Outcomes of the included studies are demonstrated in Table 6, Table 8. 13,30,53,54 Not all the targeted outcomes were demonstrated or described in each of the included studies: The available data was collected. A compiled summary of the characteristics and outcomes of different modalities is shown in Table 9.…”
Section: 305354mentioning
confidence: 99%
“…Image findings indicative of tumor necrosis include echogenic change on ultrasound, loss of contrast enhancement on CT, and decreased intensity on T2-weighted MRI. Table VIII outlines the outcomes from studies [158,159,221] evaluating MWA for CRLM.…”
Section: Outcomes Of Ablation Therapies For Hepatic Metastases Colorementioning
confidence: 99%